Considerations of confessions and the Reid Technique applied to criminal investigation - Lívia Yuen Ngan Moscatelli (Revista Brasileira de Direito Processual Penal, 2020)
The Reid Technique is a method of interviewing and interrogation widely diffused and used in criminal investigations. Manipulation, persuasion, coercion and psychological pressure are just some of the instruments used in favor of confession, regardless of the veracity. This paper tries to clarify the following questions: What is the main inheritance from the inquisitorial criminal procedural system and how does it relate to the police interrogation in Brazil? What are the main reasons that can explain the occurrence of the false confession? What does the Reid Technique consist of? What are the possible alternative to this technique?